Exploring Of Students’ Speaking Anxiety Among Third-Grade Junior High School Students’ - Pratiwi, Tiara Putri; Saraswati, Ria; Santosa, Imam (JUPE : Jurnal Pendidikan Mandala, 2024)
Students' anxiety in speaking English has become a major concern in the context of second language learning. This research aims to identify factors that influence students' anxiety when speaking English and its impact on their speaking abilities. The research focused on grade 9 junior high school students in Indonesia. selected based on their experiences in speaking English during English class. The research method involves surveys and interviews with English students at various school levels. Using a comprehensive approach, this research aims to understand the internal and external factors contributing to students' anxiety levels when communicating in English. The findings highlight the prevalence of internal factors, notably fear of making mistakes (69.6%), and external factors like limited vocabulary (87%). This anxiety correlates with students' diminished speaking skills, evident in avoidance behaviors and less coherent speech. To mitigate these challenges, tailored learning strategies are imperative to boost students' confidence in English. Proactive measures should target building self-assurance, overcoming fear of errors, and actively expanding vocabulary. By addressing these concerns, educators can foster an environment conducive to enhanced English communication skills among students’.